2019
DOI: 10.1139/cjpp-2019-0394
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of oxidative–nitrosative stress and inflammatory response by rapamycin in target and distant organs in rats exposed to hindlimb ischemia–reperfusion: the role of mammalian target of rapamycin

Abstract: Mammalian target of rapamycin (mTOR) has been recognized with potential immunomodulatory properties playing an important role in various physiopathological processes including ischemia–reperfusion (I/R) injury. I/R injury stimulate reactive oxygen and nitrogen species by activating nicotinamide adenine dinucleotide phosphate oxidase and inducible nitric oxide synthase, respectively. Controversial results have been obtained in different I/R models following localized I/R; however, the precise role of the mTOR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In the present study, the evidence that mTOR inhibitor rapamycin prevents the harmful effects of HL I/R in rats in both target and remote organs supports mTOR's critical role. This observation is consistent with the results of our previous studies and other researchers' findings that report the increment in the activity of mTOR signaling in in vitro and in vivo HL I/R injuries 19,23,32 . However, the role of mTOR activation in HL I/R remains controversial.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, the evidence that mTOR inhibitor rapamycin prevents the harmful effects of HL I/R in rats in both target and remote organs supports mTOR's critical role. This observation is consistent with the results of our previous studies and other researchers' findings that report the increment in the activity of mTOR signaling in in vitro and in vivo HL I/R injuries 19,23,32 . However, the role of mTOR activation in HL I/R remains controversial.…”
Section: Discussionsupporting
confidence: 94%
“…Previously, we examined whether mTOR has a protective or deleterious role during HL I/R injury and provided the first evidence that mTOR contributes to inflammatory response and oxidative/nitrosative stress in both target and remote organs injuries in the murine model 23 . In the current study, we examined further looked out the molecular mechanism involved in the contribution of mTOR in HL I/R-induced organ injuries related to MEK1/ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that mTOR inhibition is associated with the up-regulation of autophagy and protective effects in experimental ischemia and reperfusion [7]. Rapamycin, an immunosuppressive agent and mTOR inhibitor, exerts cytoprotective effects in both cell and animal models of ischemia [18,19]. The available data suggest that rapamycin activates protective autophagy and inhibits ER stress in ischemic neurons, hepatocytes and nephrons [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mTOR activation can significantly upregulate the expression of the proapoptotic proteins Bax and Bad, which can trigger apoptosis. Furthermore, rapamycin, an inhibitor of mTOR, can protect cells against oxidative stress-induced damage by inhibiting apoptosis [ 57 , 58 ]. Park et al proved that an abnormal increase in mTOR could evoke severe oxidative stress, neuroinflammation, and neuronal death in the hippocampus in an animal model of transient ischemia (TI) established in gerbils with high-fat diet- (HFD-) induced obesity [ 59 ].…”
Section: Signaling Pathways Of Oxidative Stressmentioning
confidence: 99%